Properties of neural noise in amblyopia - Medina, José M. (2011)
We have examined the characteristics of neural noise in amblyopia, a disorder that impairs binocular vision. Noninvasive methods based on signal-detection theory and psychophysics were used to measure threshold fluctuations in orientation processing, which is considered a main feature of cortical processing. Fluctuations were correlated and increase with the response size by power law scaling behavior. The scaling exponent in amblyopia was similar or lower than normal vision. Comparisons between observational conditions have revealed that the scaling exponent in normal binocular vision was lower than the monocular case. Surprisingly, the exponents in the amblyopic and fellow eye were lower than in amblyopic vision. The results conclude that amblyopia does not necessarily involve greater internal noise but an inverted trend.